PORTRAITS OF GRASSROOTS POWER VISUAL NARRATIVES OF WOMEN PANCHAYAT LEADERS IN RURAL INDIA - Abichandani , Kum Neelu; Chhura, Bikashdev; Singh, Deepali; Kumbhar, Sitaram; Naqvi, Lubna Sadaf; Rai, Dharmendra (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The grassroots leadership by women has become a revolution in rural India especially in the Panchayati Raj system that has seen women participating actively in it. This paper examines visual representation as an effective tool of recording, analyzing, and magnifying the lived experiences of elected women politicians. It does not rely on traditional policy and governance analyses but draws a visual-cultural approach to discuss portraits, photographs, and community-based visual stories as a means of telling a story, gaining strength, and political representation. The concepts analyzed include the ways in which visual stories can trap intersections between gender, caste, class, and local power dynamics, displaying the limited and determining women in the process of leadership. These delineations demonstrate some of the normal governing, negotiating, and survival practices, which refer to the women Panchayat leaders, not as symbolic recipients of constitutional reservations, but as time-takers of decision-making in the rural developing and social justice, and community welfare. The methodology of the work incorporates the visual analysis together with qualitative analysis based on the field documentation, interviews and participating observation to allow the development of the sensitive meaning-making and definition of representation. The results show that visual narratives are very effective in redefining how people view them and disrupting the stereotype of a passive political figure in rural women, and give confidence to young leaders. This visual documentation is a simultaneously archival, pedagogical, and political intervention, which adds to the feminist discourse, deepening democracy, and inclusive governance. The foregrounding of voices of women using images empowers the study by highlighting the possibilities of the visual culture as a tool of empowerment and social change at grassroots in rural India.